Medium-density fiberboard made from kenaf bast and core: effects of refining pressure and time on specific gas permeability - Nayeri, Majid Dehghan; Md Tahir, Paridah; Taghiyari, Hamid Reza; Alias, Aisyah Homaira; Karimi, Ali; Abdullah, Luqman Chuah; Bakar, Edi Suhaimi; Namvar, Faridah (North Carolina State University, 2014)
Studies concerning the production of medium-density fiberboard (MDF) with kenaf as an alternative fibrous material were carried out as an attempt to provide a sustainable and viable source for this lignocellulosic product. This work sought to evaluate the influence of fiber properties (including fiber length, width, wall thickness, and lumen diameter that affect aspect and flexibility ratios) on specific gas permeability in medium-density fiberboard (MDF) made from kenaf bast and core fibers, respectively. Results showed that MDF panels produced from kenaf core had significantly lower permeability than those produced from kenaf bast. This lower permeability was primarily related to the higher flexibility ratio of kenaf core fibers, which provided more surface connection area between fibers, resulting in higher integration among fibers. Lower ash and extractive contents of the core section also improved the efficiency of resin and the connection of fibers to each other; eventually lower permeability was observed in panels made from kenaf core. A high correlation was found between gas permeability and water absorption.